Opak Fault Strand Delineation Using Merapi Slope Shifted Indicator - Agus Sutiono; Bambang Prastistho; C. Prasetyadi C. Prasetyadi; Supartoyo Supartoyo (Geological Engineering Department Universitas Gadjah Mada, 2022)
Abstract After the Yogya earthquake occurred on May 27, 2006, the opinions of experts split into two groups regarding location of responsible fault to earthquake shacking; (1), First group argues that Opak Fault displacement caused the earthquake. Where fault line is commonly known runs along Opak River, striking from Parangtritis Beach to Prambanan. (2) Second group of experts stated at deferent opinion, that another fault displacement triggered the earthquake shock. Where is located at the East side of the Opak River about 10 Km. On the other-hand, this paper proposes an idea to unravel Opak Fault position by understanding, that main active fault movement underlying Bantul region has been influencing continuum mechanical process, onto Merapi Sediments surface since the early periods of continuing Merapi materials sedimentation. It should has been reflected to the surface landform at above the fault strand. Further, indicates to morphotectonic feature as an en echelon slope shifted alignment. Thus, it can be the way to assist in defining attribute of main fault (PDZ) areas by using its en echelon indicator of shifting slope alignment. This paper also presents the results of determining Opak fault line location by using Digital Elevation Model (DEM-NAS) to generate custom shading in approaching landform features. With a further doing specific landscapes observations over the entire of Young Merapi deposits. There are other challenges to alternate identification of buried basin faults fill, by doing carefully identifications in morphotectonic aspects over the entire South Slope Merapi flank. It traces from Kepurun village at about elevation 400 m towards Parangtritis at 25 m of elevation. Independent field morphotectonic data sets of such scarp, terraces, water springs alignment and active cracks are encountered in the vicinity of Merapi sediments slope shifted, particularly in Tirtomartani Jetis village Kalasan. Identification of such structures obtained from morphotectonic analysis results are regarded as reliable indicator of faults, which is efficiently can be found in field.Key word: Opak Fault, Morphotectonic, Slope Shifted, Delineation.